Analysis Of Digital Literature Factors On Junior High School Students - Siti Alifah; Yetti Supriyati; Agus Dudung; Ibnu Salman; Agus Widodo (Peneliti.net, 2021)
Students need to be equipped with digital literacy. If students are not equipped with digital literacy, it is feared that they will encounter some problems. Debriefing is needed since students know the internet. The purpose of this study was to analyze digital literacy skills which were influenced by the role of parents, students' reading interest, ICT skills, and self-control. The method used is quantitative with survey method. The data collection technique used a questionnaire instrument and a literacy ability test. Respondents were 125 students from 3 junior high schools in Bekasi Regency. Data collection by purposive sample method. Statistical analysis uses path analysis testing, this is done to see the direct and indirect effects on digital literacy of junior high school students. The results show that the role of parents affects digital literacy, reading interest affects digital literacy, ICT skills affect digital literacy and self-control affects digital literacy. In addition, the role of parents, interest in reading, ICT skills, and self-control simultaneously affect digital literacy.